Understanding and improving interactive systems design with human-in-the-loop machine learning - Zhang, Yaqian (Nanyang Technological University, 2020)
New developments in machine learning techniques have created opportunities for the Human-Computer Interaction (HCI) community to incorporate more intelligent means to improve and enhance user experience during the interaction. This thesis starts by exploring and identifying a suitable role where machine learning algorithms can play to improve the design of interactive systems. Once the area has been identified, a suitable learning algorithm has been designed and evaluated to ensure it is able to address the constraints posed by human-in-the-loop interactive systems.